Route planner mobile web application for UiTM Malaysia / Suzana Ahmad ... [et al.] - Ahmad, Suzana; Mat Diah, Norizan; Mohamad Kamal, Nor Ashikin; Mohd Jailani, Siti Zalekha (Research Management Institute (RMI), 2009)
Services that can be accessed by users with mobile devices for the purposes of route planning are increasingly in demand. UiTM Malaysia regularly host and conduct prestigious events, which involve outside participants, and therefore the development of an accurate and concise means to guide participants around the campus is very important. Convocations, Independence Day celebrations, New Year celebrations, Seminars, local and International Conferences are examples of events regularly conducted at UiTM. A Route Planner Mobile Web Application for UiTM Malaysia has been developed to produce a list of routes from two selected points in order of the shortest first. The user can select any listed location as a starting point and any listed location as a destination. Djikstra’s algorithm has been used to find the appropriate shortest route from those two selected point. Djikstra’s algorithm together with Google Maps API and Google Earth, which are popular web mapping services providing geospatial data, have been used to develop, a prototype route planner.